Lamb-dip cavity ring-down spectroscopy of acetylene at 1.4 μm. (13th December 2021) - Fasci, E; Gravina, S; Porzio, G; Castrillo, A; Gianfrani, L
Abstract: Doppler-free saturated-absorption Lamb dips are observed for weak vibration-rotation transitions of C2 H2 between 7167 and 7217 cm −1, using a frequency-comb assisted cavity ring-down spectrometer based on the use of a pair of phase-locked diode lasers. We measured the absolute center frequency of sixteen lines belonging to the 2 ν 3 + ν 5 1 band, targeting ortho and para states of the molecule. Line pairs of the P and Q branches were selected so as to form a 'V'-scheme, sharing the lower energy level. Such a choice made it possible to determine the rotational energy separations of the excited vibrational state for J -values from 11 to 20. Line-center frequencies are determined with an overall uncertainty between 3 and 13 kHz. This is over three orders of magnitude more accurate than previous experimental studies in the spectral region around the wavelength of 1.4 μ m. The retrieved energy separations provide a stringent test of the so-called MARVEL method recently applied to acetylene.